Predictive Equation for Angle Opening Distance at 750 μm After Laser Peripheral Iridotomy in Primary Angle Closure Suspects - Gao, Xinbo; Zhou, Yuying; Zuo, Chengguo; Chen, Liming; Ren, Jiawei; Lin, Huishan; Liao, Yunru; Gong, Haijun; Hu, Huanling; Lin, Mingkai (Frontiers in Medicine, 2021)
Abstract Aim The aim of this study was to investigate the changes in anterior segment parameters as assessed by ultrasound biomicroscopy (UBM) after laser peripheral iridotomy (LPI) and to propose a prediction equation for the width of the angle after LPI. Design This was a prospective study. Participants The participants included 100 subjects with primary angle closure suspect (PACS). Methods Anterior segment UBM parameters were measured, whereas AOD750 was chosen to indicate the width of the angle associated with gonioscopic angle closure, as found in a prior study. Main Outcome Measures Angle parameters, iris parameters, anterior chamber parameters and ciliary body parameters. Results All angle parameters increased after LPI, including the mean angle opening distance at 750 µm (AOD750), mean angle opening distance at 500 µm from the scleral spur (AOD500), mean angle opening distance at 750 µm from the scleral spur (AOD750), and mean angle recess area at 750 μm from the scleral spur (ARA750). Among iris parameters and ciliary body parameters, the iris thickness at 2000 μm (IT2000), iris curvature (IC), and trabecular-ciliary process distance (ICPD) were reduced after LPI. The final equation consisted of four parameters: anterior chamber depth (ACD), iris thickness at 750 µm from the scleral spur (IT750), AOD750, and lens vault (LV). This equation explained 42.7% of the variability in the angle opening indicator AOD750 after LPI, whereas in the plateau iris configuration subgroup, the accuracy of the prediction equation reached the highest a maximum of 68.6%. Conclusions There was an increase in angle opening and iris flattening after LPI. An equation involving four angle parameters was constructed, this equation which could explained 42.7% of the variability in the angle opening indicator AOD750 after LPI whereas in the plateau iris configuration subgroup, the accuracy of the prediction equation reached a maximum of 68.6%.